Pakistan Education Policy: Perspectives and Philosophical Paradigms with Regards to Conceptual Underpinning - Naz, Nuzhat; Ellahi, Kiran Ehsan; Sharjeel, Muhammad Yousuf (Annals of Human and Social Sciences, 2022)
The development and stability of a country undoubtedly depends on its national education. Through national education, in addition to achieving national goals, the development and promotion of the national ideology and the awareness of the younger generation is made possible. In this study, it has been highlighted that the practical application of national education is somewhat indispensable in nations which have come into being on the basis of a particular ideology and which have specific components of their national identity. This study endeavoured to explore this phenomenon critically. In addition, the most important aspect of the importance of this research is that education in Pakistan, which was established on the basis of Muslim nationality, should have been based on the concept of national education as its fundamental resource since the inception which in reality did not happen. These stimuli and causes have been determined through this research. At the same time, the extent to which the basic concept of national education has been given importance or not in the educational policies and strategies formulated in the 74 years of national life of Pakistan has been reviewed in this study.